Thermoplastic Starch Film Made from Cellulose to Extend the Shelf Life of Red Chilies - Sari, Vonny Indah; Rahmah, Anania; Putri, Vivin Jenika; Azzahro, Hanifah Ulfa; Nasution, Lukman Hakim (The University of Lampung, 2024)
Thermoplastic starch (TPS) is a biofilm made from starch and cellulose. The advantage of thermoplastic starch is easily degraded. TPS has weaknesses in high water affinity and low mechanical properties, so it is necessary to add polyvinyl alcohol (PVA) in making TPS packaging. The mechanical properties of TPS-PVA can be further improved by modifying it into a composite with coconut fiber cellulose. This research was purposed to produces a film containing cellulose from coconut fiber as a reinforcing material for film composites as well as to evaluate the biodegradation properties of the resulting film. It is known that the addition of 5% w/v coconut cellulose fiber is the formulation with the best yield when compared with the 1% and 3% w/v formulations. Applying TPS film to chilies can increase the shelf life of chilies. As a product that spoils quickly, one of the efforts made to maintain the quality of chilies is to use packaging made from TPS. Storing chilies at different temperature conditions using TPS-PVA film packaging with the addition of 5% w/v coconut fiber cellulose was able to maintain the shelf life and quality of chilies for 19 days at cold temperatures. Keywords: Chilies, Cellulose, Thermoplastic starch